Inventário do cômico-sério: elementos para uma crítica carnavalesca do Teatro do absurdo e suas reverberações na contemporaneidade - Maria Gorete Oliveira de Sousa (2014)
This thesis presents a study of which theme is expressed by the title Serio-Comic1s Inventory: elements for an analysis under carnivals symbology of Theater of the Absurd and its reverberations in the contemporaneity. This is a research in two theoric bases which one is literary, and the other is theatrical. The first chapter, The Carnivalization, presents the literary theory directed by the Carnivalization of Literature, proposed by Bakhtin. The second, named Historic and theoretical fundamentals of Theater of the Absurd presents its esthetic aspect, by the side of historic and philosophic aspects, besides to observe which the link between this theater and the traditional poetics. The philosophic base reviews the concept of Absurd proposed by the Algerian philosopher Albert Camus in The Myth of Sisyphus. The third chapter, Carnival and Absurd, proceeds the analyses of plays written by Eugène Ionesco and Samuel Beckett, and these analyses are illuminated by the esthetic-literary categories of Carnivalization of Literature. The fourth chapter, The Absurd in the Brazilian Contemporaneous Theater, presents the playwrights Rafael Martins and Grace Passô, in whose playwritings are found significative dialogues with the Theater of the Absurd. Because of this an analysis of the plays Lesados and Amores Surdos, texts of these authors, respectively, is done. The methodology for this research development goes from the literary base to the dramatic, textual and performance production. At first are investigated and listed the elements of the carnival´s symbology that came from the serio-comic area, the beginning of the old genre of the popular manifestation, according to Bakhtins theory. A registration of this kind agrees with the criteria of a historic inventory, and with it is possible to investigate and observe the modernization of which elements in the dramatic texts or in the performances scenic texts. With this analysis is possible to appoint Carnivalization of Literature elements in the playwriting of Ionesco and Beckett, and it backs to the old genres of the serio-comic categories. Similar this, its possible to appoint a considerate number of Theater of the Absurd elements in the Graces Passô s and Rafael Martins playwriting, even if they are conducted by the inherent actuality of their conceptions.